Influence of Work Environment, Compensation on Employee Performance at The Pratama Medan Belawan Tax Services Office - Br Sihite, Dewi Afrina; Tinendung, Ariyanto; Kusumo, Sri Rahayu Wijoyo; Amelia, Yolanda; Lubis, Hasrita; Siregar, Zulkifli (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
This investigation hopes to consider the effects of the work environment, planning and compensation fairly, while meanwhile focusing on delegate execution at the Medan Belawan Pratama Appraisal Organization Office. The assessment was aimed at the Medan Belawan Pratama Obligation Organization Office. Meetings, surveys, and documentation completed the information collection process. The data examination technique used is various backslide assessments, including the IMB Experiences for Thing and Organization Course of Action (SPSS) PC program variation 25. Considering the outcomes of the assessment, it was found that the work environment definitively impacted the display of the Medan Belawan Pratama Appraisal Organization Office agents. The investigation consequences of t count t-table (2.656 1.987) with n = 92 and a 95% importance level upheld this. Planning influences the introduction of Medan Belawan Pratama Cost Organization Office delegates; this is maintained by t count t-table assessment (2.779 1.987) at n = 92 at a significance level of 95%. Pay seriously influences the introduction of Medan Belawan Pratama Cost Organization Office delegates; this is maintained by the assessment of t count t-table (3.278 1.987) at n = 92 with a significance level of 95%. F-count regard F table (26.528 2.71) This communicates that, together (unique), there is a positive and colossal effect of the working environment, planning and compensation on the presentation of the Medan Belawan Pratama Obligation Organization Office delegates.